ANALYSIS OF ABSTRACT REASONING FROM GRADE 8 STUDENTS IN MATHEMATICAL PROBLEM SOLVING WITH SOLO TAXONOMY GUIDE - Kusmaryono, Imam; Suyitno, Hardi; Dwijanto, Dwijanto; Dwidayati, Nurkaromah (Jurnal Infinity, 2018)
This research was a descriptive research. Description of research result was presented quantitatively and qualitatively. Subjects of the research were 30 (thirty) 8th graders of SMPN 10 (State Junior High School) in Semarang, Indonesia. Data were collected through tests, documentation, observations, and interview. Student answers documents were observed and analyzed with SOLO Taxonomy guidance. The objective of the study was to analyze and provide an interpretation of students abstract reasoning level in cognitive development based on intended learning outcomes. The result of findings from students’ answers basically showed that students' abstract reasoning on the lower, middle and upper level, was alike to stages of structure complexity improvement. There were two main changes from concrete thinking to abstract thinking: quantitative stage (uni-structural and multi-structural) occurred first, as the number of details in student responses increased and then changed qualitatively (relational and extended abstract) because the detail was integrated into a structural pattern.